2021
DOI: 10.1186/s12862-021-01908-4
|View full text |Cite
|
Sign up to set email alerts
|

The significance of biomass allocation to population growth of the invasive species Ambrosia artemisiifolia and Ambrosia trifida with different densities

Abstract: Background Ambrosia artemisiifolia and Ambrosia trifida are globally distributed harmful and invasive weeds. High density clusters play an important role in their invasion. For these two species, the early settled populations are distributed at low densities, but they can rapidly achieve high population densities in a short period of time. However, their response to intraspecific competition to improve the fitness for rapid growth and maintenance of high population densities remains unclear. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…These increased daily mean temperature by 2.2°C, matching the predicted future change in climate obtained from http://www.worldclim.org for the current distribution of Ambrosia (Sun et al, 2017). The cages were hand weeded to maintain monocultures of Ambrosia , an ecological situation that is not uncommon when Ambrosia invades disturbed sites (Essl et al, 2015; Savić et al, 2021; Zhao et al, 2021). Ambrosia plants were allowed to shed seeds and regenerate naturally within each field cage.…”
Section: Methodsmentioning
confidence: 99%
“…These increased daily mean temperature by 2.2°C, matching the predicted future change in climate obtained from http://www.worldclim.org for the current distribution of Ambrosia (Sun et al, 2017). The cages were hand weeded to maintain monocultures of Ambrosia , an ecological situation that is not uncommon when Ambrosia invades disturbed sites (Essl et al, 2015; Savić et al, 2021; Zhao et al, 2021). Ambrosia plants were allowed to shed seeds and regenerate naturally within each field cage.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the biomass distribution of the root can be increased in the whole plant. Moreover, Zhao et al (2021) presented that plants can invest more photosynthetic products into their stems to compete for light resources, particularly in denser plant population with better growth. This may explain the increase of B. pilosa biomass allocation in the stem and the decrease in the leaf.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, A. artemisiifolia seems to readily colonize an area through characteristics related to seed production (propagule pressure), germination, and seedling survival ( Kempel et al, 2013 ). Studies have shown that A. artemisiifolia undergoes a rapid growth phase from the vegetative stage to the reproductive stage ( Zhao et al, 2021 ), when biomass accumulation is higher in short time, and that herbicide application at this time may activate its growth-defense trade-off mechanism ( Coley et al, 1985 ; Figueroa-Macías et al, 2021 ), i.e., the activation of defense mechanisms at the cost of suspending growth. This reduces the effective accumulation of biomass in each organ and ultimately reduces seed production ( Zhao et al, 2021 ), or might even render the plant unable to produce any seeds at all.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that A. artemisiifolia undergoes a rapid growth phase from the vegetative stage to the reproductive stage ( Zhao et al, 2021 ), when biomass accumulation is higher in short time, and that herbicide application at this time may activate its growth-defense trade-off mechanism ( Coley et al, 1985 ; Figueroa-Macías et al, 2021 ), i.e., the activation of defense mechanisms at the cost of suspending growth. This reduces the effective accumulation of biomass in each organ and ultimately reduces seed production ( Zhao et al, 2021 ), or might even render the plant unable to produce any seeds at all. Moreover, this process is not aimed at killing all A. artemisiifolia plants, so the required herbicide dosage should be lower than the guideline dosage.…”
Section: Introductionmentioning
confidence: 99%